Training practices used by elite sprint coaches - Agudo-Ortega, A.; Salinero, J. J.; Sandbakk, Ø.; Muñoz de la Cruz, V.; González-Rave, J. (International Journal of Performance Analysis in Sport, 2024)
Scientific knowledge of the training of elite athletic sprinters is limited, and much of their training relies on the intuition and expertise of experienced coaches. Therefore, the objective of this study is to provide an overview of the training practices employed by elite Spanish sprint coaches. A descriptive analysis was conducted using customised questionnaires from 14 sprint-specialised coaches who volunteered to participate. These coaches used both traditional (50%) and block periodisation (50%). Many coaches (78.6%) divided training into three phases within each of the two macrocycles. Additionally, all coaches incorporated a tapering phase of varying durations. During the general preparation phase, the focus was on strength training (78.6%) and tempo training (85.7%). In the specific preparation phase, priority was strength-speed (92.9%) and speed-endurance (100%). The competitive phase emphasised speed-strength (100%), acceleration and maximal velocity (92.9%). Coaches incorporated technique work prior to sprint sessions (100%) and conducted specific monitoring/testing sessions (78.6%). Most coaches also monitored indicators of fatigue (78.6%) and recovery parameters (100%). In conclusion, elite Spanish sprint coaches employ relatively similar strength and sprint training methods throughout the season, gradually shifting the focus towards competition specificity. However, these coaches implement different macro-periodisation models.